ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA ISLAM PB SOEDIRMAN JAKARTA TIMUR - Aang Darsono (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education (IRE) learning at SMA Islam PB Soedirman East Jakarta. The research focuses on lesson planning, learning implementation, assessment practices, supporting factors, and obstacles in implementing the Merdeka Curriculum. This study employed a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation. The research participants included the principal, vice principal for curriculum affairs, Islamic Religious Education teachers, and students. Data were analyzed using the Miles, Huberman, and Saldaña model consisting of data condensation, data display, and conclusion drawing. The findings indicate that the implementation of the Merdeka Curriculum in Islamic Religious Education learning has been carried out through the preparation of Learning Objective Flow (ATP), teaching modules, differentiated instruction, and diagnostic, formative, and summative assessments. Learning activities are student-centered through discussions, presentations, case studies, and project-based learning. Supporting factors include school leadership commitment, teacher competence, adequate facilities, and a strong religious school culture. Meanwhile, the obstacles include limited instructional time, uneven teacher understanding of differentiated learning, and diverse student learning abilities. The study concludes that the implementation of the Merdeka Curriculum in Islamic Religious Education learning has been carried out effectively and supported by a conducive school environment. A significant finding of this study is that the school's religious culture strengthens the implementation of the Merdeka Curriculum in Islamic Religious Education learning.